Effects of Nanoparticles on the Mechanical Properties of the Composites Prepared from Biological and Chemical Gels - Osma, Busra; Yavuz, Basar; Kaba, Tugsan; Evingur, Gulsen Akin (TAYLOR & FRANCIS INC, 2025)
Poly (N-isopropyl acrylamide) (PNIPAm) and polyacrylamide (PAAm) are widely used in antifouling research because of their non-harmful nature and their high water-absorbing capacity. In addition, hydrogels such as these two, should be investigated for their mechanical properties because their mechanical properties influence the antifouling paint containing them remaining on the surface of the vessels. In this research PAAm, PNIPAm, and kappa carrageenan (kappa C) doped with graphene oxide (GO) and multi-walled carbon nanotubes (MWCNTs) composite gels were examined for their mechanical properties for use in antifouling paints as a potential material. For increasing the mechanical properties of composites, GO and MWCNTs are often used as doping materials. In the research described here, a compressive test was used to determine the elasticity, and the modulus was calculated. The toughness was calculated from the slope of the stress-strain curve. The PAAm, PNIPAm, and kappa C doped with GO and MWCNT exhibited excellent swelling and deswelling behavior and good mechanical properties as composites. The results showed that the composites' mechanical characteristics increased with an ideal loading concentration of GO and MWCNTs. This study was inspired by our belief of a shortage of research on antifouling materials that are sensitive to the environment. We wanted to create materials that were both effective against fouling and environmentally safe by integrating the beneficial characteristics of hydrogels with potential materials inside antifouling paint. This study, we suggest, is an important step toward the development of antifouling materials with high mechanical performance that are also environmentally friendly.
Keywords: Biological gels; chemical gels; composites; graphene oxide; modulus; multi walled carbon nanotubes; toughness; MOLECULAR-SIZE DISTRIBUTION; CARBON NANOTUBE MWNT; ELASTIC PROPERTIES; KAPPA-CARRAGEENAN; CROSS-LINKING; POLYMERS; BEHAVIOR; Polymer Science